LINGUISTIC AND CULTURAL CLASSIFICATION OF FAMILY RELATIONS IN THE ENGLISH, RUSSIAN AND UZBEK LANGUAGES (Journal of Universal Science Research, 2026)
The article is devoted to the complex investigation of the concept “family” in comparative aspect on the material of three languages: Uzbek, Russian and English. The article analyzes and reveals similarities and differences in containing components of the concept “family” in Uzbek, Russian and English proverbs.